2019
DOI: 10.1177/1932296818822538
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Low-Intensity, Technology-Based Intervention for Increasing Physical Activity in Adults at Risk for a Diabetic Foot Ulcer: A Mixed-Methods Study

Abstract: Background: Among adults with diabetes, 19-34% will develop a diabetic foot ulcer (DFU), which increases amputation risk and health care costs, and worsens quality of life. Regular physical activity, when increased gradually, may help prevent DFUs. In this mixed-methods study, we examined the feasibility of a low-intensity, technology-based behavioral intervention to increase activity in adults at risk for DFUs. Method: Participants at risk for a DFU (n = 12; 66% female; mean age = 59.9 years) received four in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 67 publications
0
27
0
3
Order By: Relevance
“…Daily steps contribute to moderate-intensity physical activity as recommended by the World Health Organization, 10 and increases in such activity are associated with higher quality of life 1,11,12 and favourable physical outcomes, such as improved blood glucose control. 1,13 This explains the growing interest in developing interventions to stimulate people to be more active without having to participate in a specific physical activity intervention program, 14 to enhance people's 'activity-rich days'. 15 Interventions aiming to improve the daily activity of people who are at risk of foot ulceration would benefit from reference data on the weight-bearing activity in this population, to help interpret individual or group outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Daily steps contribute to moderate-intensity physical activity as recommended by the World Health Organization, 10 and increases in such activity are associated with higher quality of life 1,11,12 and favourable physical outcomes, such as improved blood glucose control. 1,13 This explains the growing interest in developing interventions to stimulate people to be more active without having to participate in a specific physical activity intervention program, 14 to enhance people's 'activity-rich days'. 15 Interventions aiming to improve the daily activity of people who are at risk of foot ulceration would benefit from reference data on the weight-bearing activity in this population, to help interpret individual or group outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…14 Scheineder, 2019. (26) A Mixed-Methods Study/ 12 pasien Intervensi berbasis teknologi menggunakan SMS digunakan dalam kontrol aktivitas fisik, kadar glukosa darah dan penghitung jejak langkah kaki.…”
Section: No Author Design/ Sample Intervention Resultsunclassified
“…Hasil menunjukkan bahwa peserta merasakan manfaat dari intervensi. Karena mampu memberikan lebih banyak informasi terkait aktivitas fisik dan mengatasi rasa sakit (26) .…”
Section: Guided Treatmentunclassified
See 1 more Smart Citation
“…For weight-bearing activity, we included five publications investigating a direct association with ulcer development (two prospective cohorts, two randomized controlled trials, one prospective mixed method). Lemaster et al [33], Waaijman et al [12], Mueller et al [34] and Schneider et al [35] (n = 602, e = 131) found no association between level of weight-bearing activity (number of steps) and risk of ulcer development (see for details Table S5). Armstrong et al [32] (n = 100, e = 8) found that a lower average daily activity level was associated with increased risk of ulcer development.…”
Section: Weight-bearing Activitymentioning
confidence: 98%